Review of Progress in Quantitative Nondestructive Evaluation 1990
DOI: 10.1007/978-1-4684-5772-8_104
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency-High Temperature Ultrasonic Transducers

Abstract: Ultrasonic testing is a promising :\DE technique for ceramic structural components. The lifetime of such components is controlled by defects and flaws. The critical flaw sizes for high performance ceramics are 25 pm and to detect such small flaws, the frequency of the transducers has to be > 30 :vi Hz [1-4]. Such transducers are usually made from ZnO, LiNb03, LMN composites [5], and PVDF piezoelectric materials However there are no reports of aluminium nitride (All\') films being used for such applications In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Further, tests of bulk single crystal AlN in a TRIGA Training, Research, Isotopes, General Atomics (TRIGA) nuclear reactor core showed this material to be completely unaffected by fast and thermal neutron fluences of 1.85 x 10 18 n/cm 2 and 5.8 x 10 18 n/cm 2 , respectively, and a gamma dose of 26.8 MGy [9]. This work, along with that of Yano [16] and Ito [17], have indicated that the 14 N(n,p) 14 C is not of concern; and AlN is an excellent candidate material.…”
Section: ) Aluminum Nitridementioning
confidence: 93%
See 1 more Smart Citation
“…Further, tests of bulk single crystal AlN in a TRIGA Training, Research, Isotopes, General Atomics (TRIGA) nuclear reactor core showed this material to be completely unaffected by fast and thermal neutron fluences of 1.85 x 10 18 n/cm 2 and 5.8 x 10 18 n/cm 2 , respectively, and a gamma dose of 26.8 MGy [9]. This work, along with that of Yano [16] and Ito [17], have indicated that the 14 N(n,p) 14 C is not of concern; and AlN is an excellent candidate material.…”
Section: ) Aluminum Nitridementioning
confidence: 93%
“…In fact, the work of Parks and Tittmann with this material is the first of its sort. In the past, thin film AlN has been shown to be unaffected by gamma irradiation up to 18.7 MGy [13] and temperatures of 1000 C. [14,15] Moreover, this material has been explicitly cited in numerous independent studies as a highly radiation tolerant ceramic [12]. This is thought to be at least partially due to its wurzite crystal structure.…”
Section: ) Aluminum Nitridementioning
confidence: 99%
“…The wurtzite structure has three independent components in the piezoelectric tensor, e 33 , e 13 , and e 15 . The final component e 15 is related to shear strain which is not expected to be of great importance for a thin film, since it is so flat.…”
Section: Stress Strain Electric Displacementmentioning
confidence: 99%
“…In the past, thin film AlN has been shown to be unaffected by gamma irradiation up to 18.7 MGy 35 and temperatures of 1000 °C. 36,37 Moreover, this material has been explicitly cited in numerous independent studies as a highly radiation tolerant ceramic. 38 Further, tests of bulk single crystal AlN in a TRIGA nuclear reactor core showed this material to be completely unaffected by a fast and thermal neutron fluence of 1.85x10 18 The literature review has revealed bismuth titanate to be the most promising material tested to date.…”
Section: Aluminum Nitride (Aln)mentioning
confidence: 99%